Restaurant Menu Labeling Policy: Review of Evidence and Controversies - VanEpps, Eric M. (Curr Obes Rep, 2016)
In response to high rates of obesity in the USA, several American cities, counties, and states have passed laws requiring restaurant chains to post labels identifying the energy content of items on menus, and nationwide implementation of menu labeling is expected in late 2016. In this review, we identify and summarize the results of 16 studies that have assessed the impact of real-world numeric calorie posting. We also discuss several controversies surrounding the US Food and Drug Administration's implementation of federally mandated menu labeling. Overall, the evidence regarding menu labeling is mixed, showing that labels may reduce the energy content of food purchased in some contexts, but have little effect in other contexts. However, more data on a range of ong-term consumption habits and restaurant responses is needed to fully understand the impact menu labeling laws will have on the US population's diet.